Effects of environmental conditions on performance in winter sports - Burtscher, M. (Routledge handbook of ergonomics in sport and exercise, 2016)
Winter sports continue to enjoy growing popularity. There are an estimated 200 million skiers and 70 million snowboarders in the world today (Langran, 2012). Additionally, there are millions of cross-country skiers, ski mountaineers or participants in one or more of the other numerous winter sports. The Olympic Winter Games encompass six different sports (biathlon, curling, ice hockey, skating, skiing and sled sports), with skiing consisting of six disciplines (alpine skiing, cross-country skiing, freestyle skiing, Nordic combined, ski jumping and snowboard) and skating (figure skating, speed skating, short track speed skating) and sled sports (bobsleigh, luge, skeleton) each consisting of three disciplines. The common characteristic of these sports is that they all are performed on snow or ice at low environmental temperatures. Whereas some sports are mostly performed indoors and at low altitude (e.g. skating, curling), others are typically performed outdoors and often at moderate (1,500-2,500 m) or even high (2,500-3,500 m) altitude (e.g. skiing, ski mountaineering, cross-country skiing). Both cold weather conditions and high-altitude hypoxia can affect exercise performance and health. Thus, the knowledge on physiological and pathophysiological responses to cold and/or high altitude are of utmost importance for diseased and healthy people as well.